PHÂN TÍCH HIỆU NĂNG CÁC CƠ CHẾ PHÂN BỔ KÊNH TRONG WiMAX - Ban, Nguyễn Tiến; Ngọc, Đặng Thế (Vietnam Journal of Science and Technology, 2012)
PERFORMANCE ANALYSIS OF CHANNELS ALLOCATION SCHEMES IN WiMAX WiMAX provides wireless broadband connection for both fixed and mobile users. For fixed users (Mainly Office and Home) disconnectivity in the connection is intolerable. Such users are needed to be allocated permanent channels, so they never face disconnectivity due to unavailability of channels in the cell. For this purpose, in this work, we have performed analysis on channels allocation schemes namely Non Prioritized Scheme (NPS) and Reserved Channel Scheme (RCS) in WiMAX scenario, in context of permanent channel allocation. These schemes were previously used for those cellular networks which had no need for permanent channel allocation in the cell. Performance parameters that have been investigated include blocking probability, probability of handover failure, probability of forced termination, and probability of not completed calls.